2021
DOI: 10.55230/mabjournal.v50i2.2015
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Instrumental Activities of Daily Living (Iadl) Disability Among Elderly Attending Health Clinics in Kelantan

Abstract: Instrumental activities of daily living (IADL) is a construct that describes the functional ability to perform complex activities, requiring physical and mental capability that allows an elderly to live independently. Studies on IADL in Malaysia are still lacking. Thus, this study aimed to determine the factors influencing IADL disability among the elderly attending health clinics in Kelantan. A cross-sectional study was conducted using a guided questionnaire consisting of sociodemographic characteristics, hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…Compared to previous studies, in Poland, the elderly aged 65 years and above reported 42.4% of disability in IADL (Ćwirlej-Sozańska et al, 2019). In Malaysia, the elderly aged 70 and above are 3.52 more likely to experience functional disability in IADL (Ismail et al, 2021). The finding of this current study is also in line with previous studies that age is a determinant factor for disability in IADL (Yau et al, 2022).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Compared to previous studies, in Poland, the elderly aged 65 years and above reported 42.4% of disability in IADL (Ćwirlej-Sozańska et al, 2019). In Malaysia, the elderly aged 70 and above are 3.52 more likely to experience functional disability in IADL (Ismail et al, 2021). The finding of this current study is also in line with previous studies that age is a determinant factor for disability in IADL (Yau et al, 2022).…”
Section: Discussionsupporting
confidence: 86%
“…Although prevalence rates are different between studies, our current study and previous studies in Ireland, Poland, and Germany indicated similarity in terms of advancing age and its association with disability in IADL (Beltz et al, 2022;Ćwirlej-Sozańska et al, 2019;Ismail et al, 2021;Tornero-Quiñones et al, 2020). Our logistic regression indicated that the elderly aged 75 years and above were 4.602 times more likely to experience disability in IADL than those aged below 75.…”
Section: Discussionsupporting
confidence: 58%
“…The Duke Social Support Index (M-DSSI), a validated Malay language interviewer-administered questionnaire of 11 items, was used for assessing social support among the elderly [ 22 ]. The M-DSSI was chosen for this study because it was a short-scale tool used for the elderly and was supported as an instrument in health promotion strategies, as well as aged care research [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…We classified smoking status as current smokers (currently using any smoked tobacco products daily or less than daily), former smoker (a person who used tobacco products in the past) and non-smokers (those never smoked in the past). A validated Malay language, interviewer-administered questionnaire of 11-item Duke Social Support Index (M-DSSI) was applied for assessing social support among the elderly (18,19). The 11-item DSSI consisted of 4 questions which measure the size and structure of social network (social interaction) and 7 questions which assess respondent's perceived satisfaction with the behavioral or emotional support obtained from their social network (subjective support).…”
Section: Data Extractionmentioning
confidence: 99%